Sheldon S. Wolin: Democracy Incorporated. Managed Democracy and the Specter of Inverted Totalitarianism. Princeton University Press, Princeton and Oxford, 2008 - Alonso Rocafort, Victor (Foro Interno, 2008)
Sin resumen